2011
DOI: 10.1002/mnfr.201000560
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate sensitizes human cervical cancer cells to apoptosis induced by cisplatin

Abstract: Naturally-occurring chemopreventive agent phenethyl isothiocyanate (PEITC), derived primarily from watercress, has been shown to inhibit cell growth and induce apoptosis in cancer cells. In this study, we examined the potential of PEITC in enhancing cisplatin-induced apoptosis in cervical cancer cells. HeLa cells were exposed to PEITC, cisplatin or both. Pretreatment of cells with PEITC strongly enhanced cisplatin-induced cytotoxicity. PEITC activated the mitogen-activated protein kinases, including JNK, ERK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 38 publications
6
58
0
Order By: Relevance
“…Specifically, U0126 reversed the EBPCmediated enhancement of cell death of cervical cancer, which is aldose reductase inhibitor that enhances the cytotoxic effects of the anticancer agent doxorubicin and cisplatin in Hela cervical cancer cells [19]. Similar study reported that U0126 blocked PEITC (a product of hydrolysis mediated by myrosinase) plus CDDP (an anticancer drug) induced apoptosis [20].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, U0126 reversed the EBPCmediated enhancement of cell death of cervical cancer, which is aldose reductase inhibitor that enhances the cytotoxic effects of the anticancer agent doxorubicin and cisplatin in Hela cervical cancer cells [19]. Similar study reported that U0126 blocked PEITC (a product of hydrolysis mediated by myrosinase) plus CDDP (an anticancer drug) induced apoptosis [20].…”
Section: Discussionmentioning
confidence: 94%
“…But, U0126, one of ERK1/2 inhibitors, has shown controversial effects on transformed cell lines proliferation for cervical cancer cells in vitro [19,20] and has not been researched in clinical development for any cancers.…”
Section: Introductionmentioning
confidence: 98%
“…This implies that sulforaphane enhances the efficiency of gemcitabine against the cancer cells, especially at lower doses, thereby minimizing its cytotoxicity to normal cells resulting in better survival. Other studies have also reported a synergistic interaction between different treatment strategies (Liu et al, 2001;Kuhar et al, 2007;Kumi-Diaka et al, 2010;Wang et al, 2011). Other studies of concurrent curcumin and chemotherapeutic drugs such as cisplatin, doxorubicin, and taxol showed that curcumin enhances the antitumor activities of the latter in various cancer cells (Chan et al, 2003;Notarbartolo et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…It is also denoted that PEI of watercress can prevent from cell growth through increasing Cisplatin which is one of the most important anticancer drugs used in the treatment of human tumors [14]. Furthermore, it is concluded that the PEI existing in watercress extract increases apoptosis as a result of inhibiting cyclooxygenase and angiogenesis in cancer cells.…”
Section: Watercress (Rorripa Nasturtium Aquaticum)mentioning
confidence: 98%